La Section urbanisme du département d’architectes du London County Council dans l’après-guerre. Élaboration, codification et transmission des savoir-faire au sein d’une grande structure publique d’architecture - Anne Portnoï (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This paper analyses the processes of development and transmission of urban planning know-how in the post-war period within the Town Planning Division of the Architects’ Department of the London County Council. The numerous working documents kept in the Percy Johnson-Marshall's archives are evidence of the internal organisation of the Division. The division is faced with the need to formalise its expertise and to share and pass it on internally and promote them.